INTERNAL CONTROL IN INDUSTRIAL ORGANIZATIONS. - Swayze, W. S. (The Accounting Review, 1946)
This article presents information regarding internal control in industrial organizations. Since the question of internal control has lately attained a great deal of prominence, the impression seems to be that its importance has arisen as a result of comparatively recent events. However, internal control was not pushed upon the accounting world by the Securities and Exchange Commission, nor did its importance arise as a result of the numerous investigations of auditing and auditing procedure which came as a result of the so-called McKesson & Robbins case. The establishment of proper accounting organizations embracing adequate systems of internal check and control became of particularly early interest to the public accountant. Internal control is nothing in the world but proper accounting organization. It is that distribution of duties and organization of routine which produces accurate, timely, and informative reports and statements in the ordinary course of events, rather than as a result of a turbulent and sustained effort on the part of supervisory accounting personnel as the deadline nears, as so often happens.